Automatic Repair of Java Programs Weighted Fusion Similarity via Genetic Programming - Cao, Heling; He, Zhenghaohe; Meng, Yangxia; Chu, Yonghe (Information technology and control, 2022)
Recently, automated program repair techniques have been proven to be useful in the process of software development. However, how to reduce the large search space and the random of ingredient selection is still a challenging problem. In this paper, we propose a repair approach for buggy program based on weighted fusion similarity and genetic programming. Firstly, the list of modification points is generated by selecting modification points from the suspicious statements. Secondly, the buggy repair ingredient is selected according to the value of the weighted fusion similarity, and the repair ingredient is applied to the corresponding modification points according to the selected operator. Finally, we use the test case execution information to prioritize the test cases to improve individual verification efficiency. We have implemented our approach as a tool called WSGRepair. We evaluate WSGRepair in Defects4J and compare with other program repair techniques. Experimental results show that our approach improve the success rate of buggy program repair by 28.6%, 64%, 29%, 64% and 112% compared with the GenProg, CapGen, SimFix, jKali and jMutRepair.